TREND AND RESEARCH FOCUS ON SERVICE MANAGEMENT IN INCLUSIVE EDUCATION: A BIBLIOMETRIC EXPLORATION - Murtanti, Wilin; Satori, Djam'an; Suryadi; Kurniatun, Taufani Chusnul (Universitas Negeri Medan, 2025)
This bibliometric study explores the trends and focus of research in the field of service management in inclusive education. By analyzing publication patterns, key themes, collaboration networks and geographical distribution, this study provides a comprehensive picture of the state and development of research in this field. The study used data from Scopus and Web of Science databases in the period 1999-2024, analyzing 1,247 articles that met the inclusion criteria. The methodology included keyword co-occurrence analysis, co-citation analysis, and network visualization using VOSviewer software. The findings indicate significant and growing interest, with a notable increase in publications over the past decade, reflecting the global prioritization of inclusive education. Key themes such as inclusive education, disability, curriculum and teacher training emerged as central to the discourse, highlighting the multidisciplinary and practical nature of the research. The research also revealed substantial international collaboration, identifying influential researchers and institutions driving the field. The United States, United Kingdom and Australia emerged as key research centers, with strong networks of collaboration across the globe. Despite the progress, there are still gaps in areas such as the role of technology, its impact on students without disabilities, and evaluation of program effectiveness, indicating directions for future research. Insights from this research can inform policy makers, practitioners and researchers, contributing to the advancement of inclusive education practices and ensuring equitable and high-quality education for all students.